Importancia de los hijos en la vejez y cambios en el comportamiento reproductivo (estudio en tres comunidades rurales de México) - Zúñiga Herrera, Elena; Hernández F., Daniel (El Colegio de México A.C., 1994)
This study analyzes the importance of children in the care of elderly populations in rural communities. The study is part of a synthesis of hypotheses related to the fertility transition. The study presented on this paper includes the opinions that the subjects interviewed had on the reduction of family size and the deliberate control of births, combined with their perception of the value of children.Data for the study were compiled in a micro-regional study called "Determinants and the Use of Contraceptive Methods in Mexican Rural Areas". This research was carried out in the Temascaltepec region, which includes three towns with under 1 500 inhabitans each, in the state of Mexico. Data was obtained from surveys and life histories of random sub-samples of 60 years-old couples or people.The study describes the dynamic of domestic units and their structure of homes where there are peoples of 60 years or older. In particular, the perception of elders about the value of their chil- dren is analyzed, especially the role children play in their economic contribution to the household or their instrumental value to it at different stages of their lives. The alternatives to which the elderly are supported later in life are also studied, viewed taking into account their involvement in the economic activity and how many of the elderly have to continue working until late in life in order to support themselves.With respect the condition in which children support their parents in their old age, the economic assistance given by was studied too. Finally, the prefference regarding family size of those 60 years or older are given, as well as the view points of women on the need to control fertility and reduce family size. Three different types of cost are studied: the economic cost of supporting and caring for children, the emotional cost of their upbringing, and the health cost of multiple pregnancies and births.